2022
DOI: 10.1177/00033197211066362
|View full text |Cite
|
Sign up to set email alerts
|

A New Predictor of Mortality in ST-Elevation Myocardial Infarction: The Uric Acid Albumin Ratio

Abstract: Several studies have shown that high uric acid (UA) and low serum albumin (SA) values increase the risk of cardiovascular disease and mortality in ST-elevation myocardial infarction (STEMI). We determined whether the uric acid/albumin ratio (UAR) is a predictor of mortality in STEMI patients. All patients who presented at our center with a diagnosis of STEMI and underwent percutaneous intervention from 2015 to 2020 were screened consecutively; 4599 patients were included. A Cox proportional hazards model was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…Furthermore, UAR predicted the severity of CAD better than the CRP-to-albumin ratio (CAR) in patients with non-ST-elevated myocardial infarction 11 . UAR has also been shown to be a predictor of death in STEMI patients, as well as a potential biomarker for identifying high-risk STEMI patients 10 . However, there is a lack of evidence in the literature on the potential role of UAR in predicting the development of NOAF following a STEMI event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, UAR predicted the severity of CAD better than the CRP-to-albumin ratio (CAR) in patients with non-ST-elevated myocardial infarction 11 . UAR has also been shown to be a predictor of death in STEMI patients, as well as a potential biomarker for identifying high-risk STEMI patients 10 . However, there is a lack of evidence in the literature on the potential role of UAR in predicting the development of NOAF following a STEMI event.…”
Section: Discussionmentioning
confidence: 99%
“…The uric acid/albumin ratio (UAR) is a novel index, which has recently been developed as a marker of inflammation and oxidative stress. The UAR has been demonstrated to have a good prognostic value in predicting STEMI patients' clinical outcomes 10 . It has also been linked to the extent of CAD in ACS patients 11 .…”
Section: Introductionmentioning
confidence: 99%
“…As a new predictive index, the prognostic value of the sUAR has been investigated in patients with STEMI, non-ST segment elevation myocardial infarction, and AKI for predicting mortality. 16 , 30 , 31 Yeter et al found that a sUAR > 1.7 was significantly associated with AKI in critically ill patients. 15 Recently, Faysal et al also demonstrated that sUAR (>1.62) had a greater predictive value for contrast-induced nephropathy, and was superior to serum uric acid and albumin.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 When albumin is combined with other risk factors, such as uric acid or CRP, the prognostic value is enhanced. 6,8 On the other hand, normalized albumin levels seem to lower mortality risk compared with hypoalbuminemia. 9 In a similar context, a retrospective study, also published in Angiology, showed that the serum albumin to serum creatinine (sACR) ratio was inversely associated with clinical outcomes in 3057 patients with ST-elevation MI after primary PCI.…”
mentioning
confidence: 99%
“…2,7 When albumin is combined with other risk factors, such as uric acid or CRP, the prognostic value is enhanced. 6,8 On the other hand, normalized albumin levels seem to lower mortality risk compared with hypoalbuminemia. 9…”
mentioning
confidence: 99%